Feasibility of administering oblimersen (G3139; Genasense) with imatinib mesylate in patients with imatinib resistant chronic myeloid leukemia – Cancer and leukemia group B study 10107 - WETZLER, MEIR (2008)
The CALGB studied the feasibility and effectiveness of adding oblimersen (G3139; Genasense) to imatinib mesylate (IM) in imatinib-resistant chronic phase chronic myeloid leukemia (CML) patients. We hypothesised that IM resistant CML cells are no longer being driven to proliferate by Bcr/Abl activity alone. Instead, the anti-apoptotic protein Bcl-2 would regulate one of the pathways controlling growth and/or viability. Thus, blocking both Bcr/Abl and Bcl-2 simultaneously would result in hematologic and cytogenetic improvement. Oblimersen was administered via continuous intravenous infusion over 10 days every 21 days, along with daily IM. Doses of both drugs were escalated in 3 cohorts; the initial dose of IM was 600 mg/day. Response was defined as a decrease by > 30% in the percentage of t(9;22) metaphase cells. Twelve patients had primary and nine had secondary imatinib resistance. Ten patients received 4 mg/kg/day oblimersen/600 mg IM, six patients received 7 mg/kg/day oblimersen/600 mg IM and five patients received 7 mg/kg/day oblimersen/800 mg IM. Only two (9.5%) patients achieved a decrease by > 30% in the percentage of t(9;22) metaphase cells. Although the combination of oblimersen and IM is safe and feasible, we did not observe clinical benefit in these patients with imatinib-resistant CML using these doses and schedule.